2017
DOI: 10.1002/aenm.201701760
|View full text |Cite
|
Sign up to set email alerts
|

Complex Interplay between Absorber Composition and Alkali Doping in High‐Efficiency Kesterite Solar Cells

Abstract: kesterite material with its optimal bandgap and absorption coefficient. [2] Alkali treatment of kesterite solar cells is one of the measures to reduce the high V OC -deficit and most of today's >10% efficiency kesterite devices utilize the beneficial effects of alkali elements on absorber layer morphology and optoelectronic properties. So far the most research attention has been paid to sodium, resulting in many thorough investigations which revealed grain size enhancement, passivation of grain boundaries, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(120 citation statements)
references
References 33 publications
6
107
1
5
Order By: Relevance
“…[20][21][22] The small network of grain boundaries in the FG layer may contribute high series resistance and reduce the fill factor of solar cells. 11,23,24) It is difficult to draw conclusions about the total thickness of the entire film due to the combination of uncertainty in the precursor thickness (nominally 1.0 ± 0.1 µm) and surface roughness however, it can be clearly seen that as the thickness of the FG layer increases, the MoSe 2 layer becomes thinner. This is somewhat surprising as other works report an increase in the thickness of MoSe 2 with increasing selenization pressure.…”
Section: Resultsmentioning
confidence: 99%
“…[20][21][22] The small network of grain boundaries in the FG layer may contribute high series resistance and reduce the fill factor of solar cells. 11,23,24) It is difficult to draw conclusions about the total thickness of the entire film due to the combination of uncertainty in the precursor thickness (nominally 1.0 ± 0.1 µm) and surface roughness however, it can be clearly seen that as the thickness of the FG layer increases, the MoSe 2 layer becomes thinner. This is somewhat surprising as other works report an increase in the thickness of MoSe 2 with increasing selenization pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Although the results and the explanation on the effect of Li doping/alloying differ and even contrast to each other, partially due to variation in material preparation conditions and matrix composition, some conclusions can be drawn based on the available reports [23][24][25][26][27][28][29][30][31][32]: (1) Li alloys with CZTS and widens the band gap of (Li x Cu 1−x ) 2 ZnSn(S,Se) 4 [24,25,27]; (2) incorporation of Li to kesterite is sensitive to Na so that Li alloying is more easily achieved without Na, in the ceramic route [25] or on quartz substrate, or using a blocking layer to prevent Na diffusion from SLG [24,27]. The presence of Na diffused from SLG greatly reduces the Li doping concentration [23,26]; (3) Li doping/alloying improves photovoltaic performance regardless the doping concentration, however, the mechanism on how Li doping/alloying improves device performance remains unclear.…”
Section: Lithium (Li)mentioning
confidence: 98%
“…Morphology improvement and apparent carrier concentration increase from 3×10 15 cm −3 to 5×10 16 cm −3 was observed when increasing x from 0 up to 0.07, and a corresponding device had an active area efficiency of 12.2%. In a comprehensive study on the effects of all alkali elements in CZTSSe, Haass et al [28] found that Li is the most favorable among all alkalis, it improves the crystallization and it requires a comparatively high Sn/ (Cu+Zn+Sn) content for the maximum device efficiency. The apparent carrier concentration estimated from C-V measurements varied in a broad range 10 15 K10 18 cm −3 when changing (decreasing) the Sn content yet keeping the same Li content, indicating that the intrinsic doping rather prevails.…”
Section: Lithium (Li)mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently in 2018, Haas et al [49] presented a large study of over 700 CZTS devices from DMSO-TU inks, examining the effects of Li, Na, Cs, and Rb doping and the cross-correlation with the metal ratios. The same study also found that Li yielded the best devices and reported a new record of 12.3% active area PCE for hydrazine-free CZTSSe figure 4(c) [49]. Also, the DMF-TU system has been used to spray-coat germanium-alloyed CZGTSSe devices [22] with 11.0% PCE and a record high open circuit voltage (V oc ) of 583 mV for the 1.15 eV bandgap, which is 63% of the Shockley-Queisser (SQ) limit V oc .…”
Section: +2mentioning
confidence: 99%